2020
DOI: 10.1177/1362361320939329
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorder/Takiwātanga: An Integrated Data Infrastructure-based approach to autism spectrum disorder research in New Zealand

Abstract: New Zealand has few estimates of the prevalence of autism spectrum disorder and no national registry. The use of administrative data sources is expanding and could be useful in autism spectrum disorder research. However, the extent to which autism spectrum disorder can be captured in these data sources is unknown. In this study, we utilised three linked administrative health data sources from the Integrated Data Infrastructure to identify cases of autism spectrum disorder among New Zealand children and young p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…This method is based on administrative service use data and is not intended to identify true autism prevalence. Therefore, it likely undercounts those with autism and may also result in incorrect identifications ( Bowden et al, 2020 ). Comparable contemporary prevalence estimates from Scotland (1.22% among young people aged 16–24) and Sweden (1.76% among young people aged 18–27) suggest the method may undercount autism prevalence by approximately 35%–55% ( Idring et al, 2015 ; Rydzewska et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This method is based on administrative service use data and is not intended to identify true autism prevalence. Therefore, it likely undercounts those with autism and may also result in incorrect identifications ( Bowden et al, 2020 ). Comparable contemporary prevalence estimates from Scotland (1.22% among young people aged 16–24) and Sweden (1.76% among young people aged 18–27) suggest the method may undercount autism prevalence by approximately 35%–55% ( Idring et al, 2015 ; Rydzewska et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additional research is also required to formally validate the method employed to identify individuals with autism ( Bowden et al, 2020 ). Once a suitable data source becomes available to validate against, improvements to the accuracy of the method, such as by requiring at least two autism codes for an autism identification, could be explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that there are approximately 40,000 people with autism in New Zealand, the country in which the present study was conducted (Ministries of Health and Education, 2016). A recent study of autism in children and young people in New Zealand identified a rate of 1 in 174 in ages 0–24 years, and specifically 1 in 102 in 8 years old, with a male to female ratio of 3.6:1 (Bowden et al, 2020). The authors did highlight, however, that the figure was likely to be under representative of the true rates of autism in New Zealand due to difficulties with case identification.…”
Section: Introductionmentioning
confidence: 99%
“…In New Zealand (NZ), the government published the first official autism guidelines for clinicians in 2008 (Ministries of Health and Education, 2016). Recently, the word Takiwātanga was added as the Te Reo Māori term for autism; it derived from tōku/tōna anō takiwā-in my/his/her own time and space (Bowden et al, 2020).…”
Section: Historic Backgroundmentioning
confidence: 99%